INCREMENTAL DAMAGE THEORY OF PARTICULATE-REINFORCED COMPOSITES WITH A DUCTILE INTERPHASE - YANG Hui (Jixie qiangdu)
This paper deals with a new micromechanics model of particulate- reinforced composites（ PRCs） which can describe the evolution of debonding damage,matrix plasticity and particle size effect on the deformation. Based on the preceding researches,a ductile interphase was considered in the frame of incremental damage theory to describe the dependence of elasticplastic-damage behavior on particle size. Progressive damage was controlled by a critical energy criterion for particle-matrix interfacial separation. The equivalent stresses of the matrix and interphase were determined by field fluctuation method. The influences of progressive debonding damage,particle size and interphase properties on the overall stress-strain response of PRC were analyzed. Due to the existence of a ductile interphase, stress transfer and plastic initiation in PRC become very complicated,and a unit-cell（ UC） based FEM was used to understand their evolution and demonstrate the role of the interphase.Finally,particle size effect on the mechanical behaviors of composites was interpreted.